Morphological study of aorta in patients with acute aortic syndromes - Buchnieva, Olga (ScienceRise: Medical Science, 2019)
Purpose of the study is to investigate the morphology of the aortic wall in patients with acute aortic syndrome. Materials and methods. The results of morphological study of aneurysmatic fragments (n-52), which were collected intraoperatively, each fragment were prepared on the basis of the SI "V.T.Zaycev Institute of General and Urgent Surgery AMSU", which were coloured with hematoxilin eosin, elastic fibers/ were incubated with antibodies to IgG, and with Apo-Alert DNA Fragmentation to determine apoptosis. Results. Post-coarctation aneurysms had the following microscopic picture: a decrease in the medial layer with small fields of disorganization of elastic fibers and smooth muscle cells (SMC). The detection of apoptotic cells in the sections is minimal. In the group of acute aortic dissection aneurysms in 40 % of cases, the elastic fibers were fragmented, the SMC are chaotic with separate parts of the isiocytane medineocrine - a typical pattern for Marfan's syndrome. A microscopic study of thoracoabdominal aneurysms showed a significant decrease in the middle layer with the development of fibrosis. When counting the total number of cells, a decrease in smooth muscle cells was found on average by 54 %. The aneurysms of the abdominal aorta were characterized by major degenerative changes. Reducing the medial layer and fibrous changes were also the most significant. Reduction of the medial layer and fibrous changes were most significant in this group Conclusions. All types of complicated aneurysms are characterized by insufficiency of smooth muscle cells in aortic wall. The study found that a decrease in the number of smooth muscle cells can occur due to apoptosis. There is a clear correlation with inflammatory infiltration by cells that produce apoptosis induction